From oceans to dinner plates: The impact of microplastics on human health - Ebuka Chizitere Emenike; Chika J. Okorie; Toluwalase Ojeyemi; Abel Egbemhenghe; Kingsley O. Iwuozor; Oluwaseyi D. Saliu; Hussein K. Okoro; Adewale George Adeniyi (Heliyon, 2023)
Microplastics, measuring less than 5 mm in diameter, are now found in various environmental media, including soil, water, and air, and have infiltrated the food chain, ultimately becoming a part of the human diet. This study offers a comprehensive examination of the intricate nexus between microplastics and human health, thereby contributing to the existing knowledge on the subject. Sources of microplastics, including microfibers from textiles, personal care products, and wastewater treatment plants, among others, were assessed. The study meticulously examined the diverse routes of microplastic exposure—ingestion, inhalation, and dermal contact—offering insights into the associated health risks. Notably, ingestion of microplastics has been linked to gastrointestinal disturbances, endocrine disruption, and the potential transmission of pathogenic bacteria. Inhalation of airborne microplastics emerges as a critical concern, with possible implications for respiratory and cardiovascular health. Dermal contact, although less explored, raises the prospect of skin irritation and allergic reactions. The impacts of COVID-19 on microplastic pollution were also highlighted. Throughout the manuscript, the need for a deeper mechanistic understanding of microplastic interactions with human systems is emphasized, underscoring the urgency for further research and public awareness.